Penilaian Ranah Afektif dalam Bentuk Penilaian Keterampilan Menulis dengan Model Pembelajaran Think Talk Write (TTW) Menggunakan Media Audiovisual pada Siswa Sekolah Dasar - Veronika Unun Pratiwi; Nofrahadi; Apri Pendri; Dina Komalasari; Sumarwati (Program Studi Pendidikan Bahasa dan Sastra Indonesia FKIP Universitas Islam Riau, 2021)
Permendikbud No. 66/2013 concerning assessment standards explains that the assessment techniques and instruments used in the 2013 Curriculum include competency assessment of attitudes, knowledge, and skills. This means that learning and assessment must develop students' competencies related to the affective, cognitive, and psychomotor domains. Assessment of the affective domain is important because assessing the affective domain must be carried out in learning activities. The education unit needs to design and develop an appropriate affective domain assessment to achieve optimal learning objectives. In this study, the affective domain rating scale uses skills assessment using a Likert scale. Think Talk Write is a learning model that can improve activity and communication among students. Ngalimun argues that the Think Talk Write learning model is a type of learning model that starts with thinking through the reading material, communicated with presentations, discussions, and then reports on the presentation results.